Red Reflex Examination in Neonates for 2 Years Screening - Ashraf Mohammadzadeh; Ahmad Shahfarhat; Reza Saeidi; Azin Vaezi (Mashhad University of Medical Sciences, 2020)
Background: Red reflex is a simple test that can detect potentially life-threatening ocular abnormalities. In 2012, a red reflex screening campaign started in Umbria, central Italy. In the present study, we report the results of eye examination in the routine first visit of newborns in a private hospital within 2014-2016.Methods: The red reflex test was carried out as a part of the first health visit of newborns in a private hospital for 2 years. The eyes of all newborns were examined on the first day of life by a handheld ophthalmoscope. The suspected cases with cataract were referred to the Ophthalmologic Department of Mashhad University of Medical Sciences, Mashhad, Iran, for the confirmation of the diagnosis.Results: During the 2 years of the study, a total of 10,484 neonates were delivered in this hospital 10 of whom were referred for ophthalmology consultation due to suspected abnormal red reflex. In 2 cases (0.019%), the diagnosis of congenital cataract was confirmed by an ophthalmologist.Conclusion: The results of the current study are consistent with the findings of previous studies, although the reports on red reflex screening are sporadic in the literature. Due to low cost and easy performance and in spite of high false-positive red reflex test, it appears to be useful for the early diagnosis of congenital low-vision disease for the prevention of vision impairment. In addition, the present study confirmed that the red reflex test should become a part of the first newborn examination immediately after birth.